On certain development aspects of an ipsas-based system-target approach to evaluation of net asset sustainability level projects in high-rise construction - Kazaryan Ruben (E3S Web of Conferences, 2018)
Problems of accounting and reporting of net assets and the procedure of their formation taking into account the specifics of the economic and legal status of property of a non-commercial autonomous institution are some of the most controversial in the accounting for entities of the public sector. The study focuses on justification of accounting rules for net assets of public sector entities. The methods used in the study are as follows: comparison, synthesis, analysis, logical approach, and system approach. The article examines legal aspects and specifics of recognition of assets of public sector entities in accordance with IPSAS standards (International Public Sector Accounting Standards are a set of accounting standards issued by IPSASB (Council for International Financial Reporting Standards for Public Sector Organizations) used by state-owned enterprises worldwide in preparation of financial statements as of the 31st of August, 2015. The most crucial factor in the modeling of key performance indicators of the system-target approach to estimation of the sustainability level of net assets on the basis of IPSAS is a multicriterial evaluation of the basic management strategy for quality system elements used in operational and strategic planning projects operations in high-rise construction. We offer an alternative evaluation of assets due to be returned to the right holder (the state controller) in the event of liquidation of a public sector entity.